Eukaryotic Class II Cyclobutane Pyrimidine Dimer Photolyase Structure Reveals Basis for Improved Ultraviolet Tolerance in Plants - Hitomi, Kenichi (American Society for Biochemistry and Molecular Biology, 2012)
Ozone depletion increases terrestrial solar ultraviolet B (UV-B; 280–315 nm) radiation, intensifying the risks plants face from DNA damage, especially covalent cyclobutane pyrimidine dimers (CPD). Without efficient repair, UV-B destroys genetic integrity, but plant breeding creates rice cultivars with more robust photolyase (PHR) DNA repair activity as an environmental adaptation. So improved strains of Oryza sativa (rice), the staple food for Asia, have expanded rice cultivation worldwide. Efficient light-driven PHR enzymes restore normal pyrimidines to UV-damaged DNA by using blue light via flavin adenine dinucleotide to break pyrimidine dimers. Eukaryotes duplicated the photolyase gene, producing PHRs that gained functions and adopted activities that are distinct from those of prokaryotic PHRs yet are incompletely understood. Many multicellular organisms have two types of PHR: (6-4) PHR, which structurally resembles bacterial CPD PHRs but recognizes different substrates, and Class II CPD PHR, which is remarkably dissimilar in sequence from bacterial PHRs despite their common substrate. To understand the enigmatic DNA repair mechanisms of PHRs in eukaryotic cells, we determined the first crystal structure of a eukaryotic Class II CPD PHR from the rice cultivar Sasanishiki. Our 1.7 Å resolution PHR structure reveals structure-activity relationships in Class II PHRs and tuning for enhanced UV tolerance in plants. Structural comparisons with prokaryotic Class I CPD PHRs identified differences in the binding site for UV-damaged DNA substrate. Convergent evolution of both flavin hydrogen bonding and a Trp electron transfer pathway establish these as critical functional features for PHRs. These results provide a paradigm for light-dependent DNA repair in higher organisms.